The determinants of tax non-compliance: Evidence from Malaysia / Azman Gul Zaman Khan - Azman , Gul Zaman Khan (2020)
Tax non-compliance is an act of disobeying the tax laws provided by the legislation either intentionally or unintentionally. The objective of this study is to examine the relationship of four independent variables; tax knowledge, ethics, government quality and change in government to the dependent variable; tax non-compliance. The research framework of this study is developed based on five variables and employed theory of planned behavior. Four hypotheses are tested based on the research framework. The research instrument of this study is structured questionnaire. The questionnaires are distributed to taxpayers in Klang Valley. A total of 415 samples were collected from taxpayers through two sampling techniques which are purposive sampling and snowball sampling. Based on the analysis, three independent variables; ethics, government quality and change in government have significant impact to the dependent variable; tax non-compliance while the remaining independent variable; tax knowledge has no significant impact to the dependent variable; tax non-compliance. Next, the study addresses some limitation to the study in which the sample size that represents the whole population of individual taxpayers in Malaysia may not be sufficient to generalize the whole taxpayers. Hence, suggestion for future research is to increase the sample size so that the future research able to generalize the whole population and able to come out with a stronger regression model.